Physician- and Patient-Reported Severity and Quality of Life Impact of Alopecia Areata: Results from a Real-World Survey in Five European Countries - Sergio Vañó-Galván; Ulrike Blume-Peytavi; Paul Farrant; Pascal Reygagne; Erin Johansson; Catherine Reed; Simran Marwaha; Frederick Durand; Bianca Maria Piraccini (Dermatology and Therapy, 2023)
Abstract Introduction Alopecia areata (AA) can negatively affect quality of life (QoL) and is associated with increased prevalence of anxiety and depression (vs people without AA). This study compared physician-assessed and patient self-rated severity of AA in a European sample and described the patient-reported burden of AA stratified by physician-assessed severity. Methods Real-world data were collected from the Adelphi Real World AA Disease Specific Programme™, a retrospective point-in-time cross-sectional survey of dermatologists and their adult patients with AA in five European countries (France, Germany, Italy, Spain, UK). Physicians provided clinical data and an AA severity assessment, according to their own definition of ‘mild’, ‘moderate’ and ‘severe’. Patients were invited to provide their perception of AA severity and completed patient-reported outcome (PRO) questionnaires, including Skindex-16 for AA (Skindex-16 AA), EuroQol-5-dimension questionnaire 5-level (EQ-5D-5L), Hospital Anxiety and Depression Scale and the Work Productivity and Activity Impairment Questionnaire. Results Data for 2083 patients were collected by 239 physicians; 561 of these patients completed PRO questionnaires. In 78.5% of cases with available data (N = 549), there was alignment between patient and physician-rated AA severity (severity was rated higher by physicians in 15.7% of cases, by patients in 5.8% of cases). Data from all PRO instruments showed an increase in patient-reported burden and work and activity impairment with increasing physician-rated AA severity. For the Skindex-16 AA, the Emotions scale had the worst scores; anxiety/depression was the EQ-5D-5L dimension with the highest percentages of patients reporting any perceived problem. Conclusions These data highlight the significant impact that AA can have beyond hair loss, especially for patients with severe AA. There was substantial physician–patient alignment on severity assessment. Higher physician-rated AA severity was associated with higher levels of patient-reported disease burden, including anxiety and depression, and work and activity impairment. These data may help inform appropriate treatment strategies.